Jobs Undone : Reshaping the Role of Governments toward Markets and Workers in the Middle East and North Africa - World Bank (Washington, DC: World Bank, 2022)
A decade since the spark of the Arab Spring, the Middle East and North Africa (MENA) region continues to suffer from limited creation of more and better jobs. Youth face idleness and unemployment. For those who find jobs, informality awaits. Few women attempt to enter the world of work at all. Meanwhile, the available jobs are not those of the future. These labor market outcomes are being worsened by the coronavirus (COVID-19) pandemic.